1997
DOI: 10.1159/000244485
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prematurity, Stress and Sepsis on the Neutrophil Respiratory Burst Activity of Neonates

Abstract: The aim of this study was to evaluate the impact of prematurity, sepsis and stress on the neutrophil respiratory burst activity (NRBA) of neonates. For this purpose 122 healthy neonates (89 term and 33 preterm), 33 preterm stressed neonates, 59 septic neonates (12 term and 47 preterm) and 26 healthy adults were studied. The NRBA was assessed after in vitro stimulation by PMA using a whole blood flow cytometric microassay with dihydrorhodamine 123 (DHR 123). It was found that the percentage of responding neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
11

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 24 publications
1
33
0
11
Order By: Relevance
“…Most of the groups demonstrated normal or even enhanced NRBA by neutrophils of term and preterm infants (9,17,39 -41), and a positive correlation to gestational age was observed (2). In contrast, other researchers depicted normal NRBA in healthy term neonates but diminished NRBA in both preterm infants and infected or stressed neonates (7,8,11,12). In our study, we excluded the influence of labor on the phagocyte function by analyzing fetal blood (25,26).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Most of the groups demonstrated normal or even enhanced NRBA by neutrophils of term and preterm infants (9,17,39 -41), and a positive correlation to gestational age was observed (2). In contrast, other researchers depicted normal NRBA in healthy term neonates but diminished NRBA in both preterm infants and infected or stressed neonates (7,8,11,12). In our study, we excluded the influence of labor on the phagocyte function by analyzing fetal blood (25,26).…”
mentioning
confidence: 85%
“…Several qualitative deficiencies of phagocyte function were demonstrated earlier in preterm infants and stressed or septic neonates. The functional deficiencies comprised migration, phagocytosis, and bactericidal potency, for example, release of bactericidal/permeabilityincreasing protein (7)(8)(9)(10)(11)(12)(13)(14)(15). However, normal or even enhanced spontaneous neutrophil respiratory burst activity in term and preterm neonates was reported in other studies (16,17).…”
mentioning
confidence: 86%
“…That is to say, neonates have a larger population of inactive phagocytic cells which can be detected through functional studies but which are not related to morphological immaturity ). This was supported by studies which showed neonates to have a larger population of non-motile cells in chemotaxis assays (Krause et al, 1986b(Krause et al, , 1989) and a higher percentage of cells that do not produce an oxidative respiratory burst when stimulated (Gessler et al, 1996;Drossou et al, 1997). However, this does not explain why the inactive cells are different.…”
Section: Conclusion and Therapeutic Prospectsmentioning
confidence: 97%
“…Thus, we selected 28 healthy individuals for the comparative group, which could not be age matched. Previous studies have shown that the respiratory burst activity of leukocytes from children and adolescents does not differ significantly from that of adults (22,23). This similarity allowed us to compare the NADPH oxidase activity of leukocytes from children with asthma to measurements in healthy adult individuals.…”
Section: Discussionmentioning
confidence: 94%